Critical Reflections on Cinema Belgica: The Database for New Cinema History in Belgium - Vincent Ducatteeuw; Daniel Biltereyst; Philippe Meers; Christophe Verbruggen; Dries Moreels; Julia Noordegraaf; Sally Chambers; Pieterjan De Potter; Tamar Cachet; Nicolas Franck; Florian Deroo (Journal of Open Humanities Data)
New Cinema History broadened film studies by emphasising the complexity of cinema as a multifaceted phenomenon that includes the socio-economic context in which films were made, circulated, shown and received. As part of the digital turn, the discipline adopted computational methods and created quantitative research data to research this socio-economic context at scale. However, not all datasets created in this context adhere to FAIR principles, decreasing their reusability. By reconciling 14 cinema-related datasets, Cinema Belgica facilitates research into the history of Belgian cinema. This research paper documents and critically reflects on the choices made when selecting, modelling and reconciling information for the Cinema Belgica database.